Effect of surface roughness using different electrodes on electrical discharge machining - Mohd Abd Latif, Abd Ghani (2008)
The electrical discharge machining (EDM), is one of the processing based on non-traditional manufacturing procedures, is gaining increased popularity, since it does not require cutting tools and allows machining involving hard, brittle, thin and complex geometry. The objective of the project is to predict the surface roughness on the workpiece using different electrode such copper, aluminum and brass. There must be a different on surface roughness produce in tool steel workpiece. Results obtained from this study will be compared among each other and similar studies in the literature. The problem of this project is to predict the best electrode among copper, brass and aluminum electros that can give the smoothes surface roughness on the tool steel workpiece. The problem face in this project is to choose and set the parameters before running the experiment. The EDM parameters such as current, pulse on-time, pulse off-time, arc voltage, also can affect the Ra, surface roughness on the workpiece. This is because the parameters are different between the electrodes each electrode has their own characteristics. The tool steel workpiece is machined by EDM using copper, brass, and aluminum electrodes. After machining, the workpiece will be measured using perthometer. Data collected will be analyzed before deciding the best electrode. The best electrode for the EDM between copper, aluminum, and brass is copper electrodes.